The ammonia leaching of alloy produced from waste printed circuit boards smelting process - Lim, Y.; Kwon, O.; Lee, J.; Yoo, Kyoungkeun (Taylor & Francis, 2013)
The ammonia leaching tests were carried out to recover valuable metals from alloy obtained from smelting reduction process of mobile phone printed circuit boards. Leaching factors such as kinds of salt, ammonia concentration, and the interaction of metals, which are components of PCB, were investigated to improve the leaching efficiency. In the leaching tests using metal powders such as Zn, Sn, Ni, and Pb to investigate the interaction of metals, zinc was easily dissolved in ammonia solution, whereas Sn and Ni were not detected or the Pb concentration decreased rapidly. The metal concentrations increased with an increase in NH3 concentration from 1 to 5 kmolm-33. The content of Cu could increase to 98% under the leaching conditions: 2 kmolm-3 NH4Cl and 5 kmolm-3 NH3 solution with 0.1 kmolm-3 CuCl2 at 200 rpm and 30°C with 1% pulp density.